Cultural diplomacy in Ferdowsi’s Shahnameh based on religion - Elaheh Heidari, Abdolnaser Nazaryani, Alireza Mozaffari, (Opción, 2019)
This paper is descriptive-analytic methodologically and aimed at helping the development and spreading of religions in other countries of the landlord in Ferdowsi’s Shahnameh. The results of this study show that the court in Iran promotes Zoroastrianism in idolatrous countries such as India, China, Kabul, as well as Roman Christian countries. Manichean religion, Christianity and Islam are also promoted in Iran. In conclusion, in Shahnameh, Christianity is the only religion that has been able to influence Iranian culture due to the connections between the countries of Rome and Iran.